Dual-patterned immunofiltration (DIF) device for the rapid efficient negative selection of heterogeneous circulating tumor cells. Issue 24 (18th November 2016) - Bu, Jiyoon; Kang, Yoon-Tae; Kim, Young Jun; Cho, Young-Ho; Chang, Hee Jin; Kim, Hojoong; Moon, Byung-In; Kim, Ho Gak
Abstract : We present an anti-CD45 antibody-based dual-patterned immunofiltration device for the enrichment of heterogeneous CTC subtypes by effective elimination of leukocytes. Abstract : The analysis of circulating tumor cells (CTCs) is an emerging field for estimating the metastatic relapse and tumor burden of cancer patients. However, the isolation of CTCs is still challenging due to their ambiguity, rarity, and heterogeneity. Here, we present an anti-CD45 antibody based dual-patterned immunofiltration (DIF) device for the enrichment of heterogeneous CTC subtypes by effective elimination of leukocytes. Our uniquely designed dual-patterned layers significantly enhance the binding chance between immuno-patterns and leukocytes due to the fluidic whirling and the increased binding sites, thus achieving superior negative selection in terms of high-throughput and high purity. From the experiments using lung cancer cells, 97.07 ± 2.79% of leukocytes were eliminated with less than 10% loss of cancerous cells at the flow rate of 1 mL h −1 . To verify the device as a potential diagnostic tool, CTCs were collected from 11 cancer patients' blood and an average of 283.3 CTC-like cells were identified while less than 1 CTC-like cells were found from healthy donors. The samples were also analyzed by immunohistochemistry and the reverse transcription polymerase chain reaction to identify their heterogeneous characteristics. These remarkable results demonstrate that the present device could help to understand the unknown properties or undiscovered roles of CTCs with a non-biased view.